ChemInform Abstract: Magnetism, Electronic Structure and Optical Properties of TbNiGe2. Issue 16 (March 2016) - Gupta, Sachin; Suresh, K. G.; Lukoyanov, A. V.; Knyazev, Yu. V.; Kuz'min, Yu. I.
Abstract: Polycrystalline TbNiGe2 is prepared by arc melting of the elements followed by annealing (evacuated quartz tubes, 800 °C, 7 d).